Ecosystem Based Adaptation for Increased Water Availability: A Case Study from the Hills and Mountains of Nepal - Khanal, Keshav Prasad; Khatri, Top Bahadur; Nepal, Santosh Mani; Poudel, Buddi Sagar; Sapkota, Raju; Thapa, Binod; Dahal, Digambar Singh; Dhakal, Bhola (Journal of Forest and Livelihood, 2025)
Water scarcity is a pressing issue in Nepal’s rural hill communities, worsened by climate change, irregular rainfall, and unplanned infrastructure. This study examines the impact of Ecosystem-based Adaptation (EbA) strategies on water availability and soil moisture in Dolakha, Salyan, and Achham districts. Using a participatory approach, data were collected through household surveys (n=392) and focus group discussions (FGDs) to assess community perceptions of EbA interventions, particularly conservation pond construction and rehabilitation. Results show that EbA measures significantly improve water availability and soil moisture, with perception scores ranging from 6.12 to 6.84 on a 10-point scale. Additionally, reduced time spent collecting water benefits women and children, improving their quality of life. These findings underscore the need to integrate EbA strategies into government policies and development programs, providing a sustainable solution to water scarcity and climate variability while enhancing community resilience.